Ways of seeing, knowing and gathering : taking art out of the classroom : exploring the scope for art education in the expanded field to benefit the transformative process of higher education - Van der Westhuijzen, Anika (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015.